2008
DOI: 10.1042/bj20071555
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein phosphatase indirectly regulates phytochrome-interacting factor 3 via phytochrome

Abstract: Light signal transduction in plants involves an intricate series of pathways which is finely regulated by interactions between specific signalling proteins, as well as by protein modifications such as phosphorylation and ubiquitination. The identification of novel phytochrome-interacting proteins and the precise signalling mechanisms that they mediate is still ongoing. In our present study, we show that the newly identified putative phytochrome-associated protein, PAPP2C (phytochrome-associated protein phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 50 publications
(60 reference statements)
1
52
0
Order By: Relevance
“…The major obstacle to defining the mode of Ser-86 phosphorylation is the lack of reliable in vitro systems to generate reproducible data on the autophosphorylation of phyB. Autophosphorylation of phyB was reported a few years ago; however, this observation has not yet been corroborated (Phee et al, 2008). This report concluded that (1) phyB Pr and Pfr autophosphorylate approximately at equal levels in vitro; (2) deletion of the N-terminal region, containing 100 amino acids, prevented phosphorylation; and (3) mapping of phosphorylation sites was not feasible.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The major obstacle to defining the mode of Ser-86 phosphorylation is the lack of reliable in vitro systems to generate reproducible data on the autophosphorylation of phyB. Autophosphorylation of phyB was reported a few years ago; however, this observation has not yet been corroborated (Phee et al, 2008). This report concluded that (1) phyB Pr and Pfr autophosphorylate approximately at equal levels in vitro; (2) deletion of the N-terminal region, containing 100 amino acids, prevented phosphorylation; and (3) mapping of phosphorylation sites was not feasible.…”
Section: Discussionmentioning
confidence: 85%
“…On the one hand, it was shown that papp-5 null mutants display hyposensitive responses to R light, whereas PAPP-5 phosphatase binds phyB in in vitro pull-down assays and these proteins colocalize in photobodies of transgenic plants (Ryu et al, 2005). On the other hand, a more recent report demonstrated that phyB also interacts with another phosphatase designated PAPP2C in vitro, and the loss-of-function mutant of papp-2c also exhibited reduced responsiveness to R light (Phee et al, 2008). Both of these phosphatases interact preferentially with the Pfr conformer of phyB, suggesting that reversible phosphorylation might play a role in modulating phyB-regulated signaling and photomorphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type oat phyA, as well as S599A, showed autophosphorylation and also phospho-transfer activity on PIF3, as previously reported. 9 Both S8A and S18A mutants showed a phospho-transfer activity similar to that of wild-type oat phyA, suggesting that these mutants retained normal protein kinase activities. Therefore, the hypersensitive light responses of the transgenic plants expressing the autophosphorylation site mutants and the slow degradation of the phyA undergoes more rapid degradations than unphosphorylated phyA or dephosphorylated phyA species by protein phosphatases, because the phosphorylated phyA proteins are more efficiently degraded by the ubiquitin/26S proteasome through the enhanced interaction with the COP1/ SPA1 complex.…”
Section: Autophosphorylation Site Mutations Do Not Influence the Kinamentioning
confidence: 94%
“…On the other hand, a few protein phosphatases bind and dephosphorylate phytochromes, including flower-specific phytochromeassociated protein phosphatase (FyPP), 7 phytochrome-associated protein phosphatase 5 (PAPP5), 8 and phytochromeassociated protein phosphatase type 2C (PAPP2C). 9 It is possible that phytochrome phosphorylation is regulated by autophosphorylation and protein phosphatase activity. Furthermore, previous studies with PAPP5 showed that phytochrome stability is increased in PAPP5-overexpression lines and decreased in papp5 knockout lines, suggesting that phytochrome phosphorylation is involved residues in phytochrome autophosphorylation, we generated a deletion mutant (∆6-12) of seven amino acid residues ( 6 PASSSSS 12 ) and a substitution mutant in which the five serine residues were replaced with alanine residues (S8-12A).…”
Section: Autophosphorylation Plays a Role In Signal Desensitization Omentioning
confidence: 99%
See 1 more Smart Citation